PENGARUH FAKTOR LINGKUNGAN BELAJAR SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA - Handayani, Fitri; Okianna, Sulistyarini; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to find out what of learning environment in SMA Hidayatul Mubtadi-ien Desa Kuala Dua Kecamatan Kubu Raya. The method of this research was descriptive. The participant of this research were the students of SMA Hidayatul Mubtadi-ien Desa Kuala Dua Kecamatan Kubu Raya. This research used questionnaire and documentary techniques. The research finding showed that the influenced of study environment of economic subject in SMA Hidayatul Mubtadi-ien Desa Kuala Dua Kecamatan Kubu Raya is 54,9% and the result showed that score of t hitung > t table (4.241 > 1,997) significant score 0,002 < 0,005 Ho ho was rejected and Ha wasÂ so it can be concluded that there is correlation between school learning environment and student learning motivation of economic subject in SMA Hidayatul Mubtadi-ien Desa Kuala Dua Kecamatan Kubu RayaKeywords: School learning environment, Learning Motivation.